2017
DOI: 10.7324/japs.2017.70210
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Condition for Enhanced Decolorization of Direct blue Dye by Aspergillus flavus and Penicillium canescens

Abstract: Six fungal species were isolated from Egyptian soil and identified as Aspergillus flavus, Aspergillus niger, Penicillium canescens, Penicillium crustosum, Penicillium sp. and Fusarium sp. and were tested for their decolorization activity of direct blue dye (DB). Aspergillus flavus and Penicillium canescens were the best active fungal species for decolorization of direct blue dye. The optimum conditions for direct blue dye decolorization by both fungi grown on Czapek's Dox liquid medium were at a concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Although mycoremediation seems promising, various physical and chemical parameters play significant roles in determining the degradation efficiency of fungal strains when the operation is performed in vitro or in situ . For example, it was previously noted by Hefnawy et al (2017) that a concentration of 0.05% direct blue dye inhibited the growth of A. flavus and Penicillium canescens , and they also found that concentrations beyond 0.01% were already toxic to the fungi, as was evidenced by decreased decolourization values. A similar consequence was observed for P. chrysosporium by Senthilkumar et al (2014) when they increased the dye concentration; however, optimizing the media and introducing possible inducers such as lignin helped to significantly increase the tolerance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although mycoremediation seems promising, various physical and chemical parameters play significant roles in determining the degradation efficiency of fungal strains when the operation is performed in vitro or in situ . For example, it was previously noted by Hefnawy et al (2017) that a concentration of 0.05% direct blue dye inhibited the growth of A. flavus and Penicillium canescens , and they also found that concentrations beyond 0.01% were already toxic to the fungi, as was evidenced by decreased decolourization values. A similar consequence was observed for P. chrysosporium by Senthilkumar et al (2014) when they increased the dye concentration; however, optimizing the media and introducing possible inducers such as lignin helped to significantly increase the tolerance.…”
Section: Discussionmentioning
confidence: 87%
“…Factors such as temperature and pH were also observed to have crucial effects on biodegradation. For example, Hefnawy et al (2017) found that A. flavus and P. canescens showed the best activity in the temperature and pH ranges of 30°C-35°C and 4-5, respectively. All these studies indicate that species with more significant biodegradation potential should be prioritized, and further intense research into optimizing the conditions of the preferred reaction pathways is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate BRB 11 had the most active isolate to grow and decolorize RBBR dyes in the medium compared to other strains (Table 2). Previous studies showed the growth rate of fungal strain has a positive correlation to the decolorization activity (Kaur et al 2015;Hefnawy et al 2017;Ramadhan et al 2021). However, in the case of fungal strain BRB 73 and BRB 81, the decolorization rate did not along with the growth rate.…”
Section: Isolation and Screening Of Fungi Ligninolytic Enzymeproducermentioning
confidence: 97%
“…Dentre as hidrolases relatadas para este fungo, destacam-se as enzimas degradadoras da parede celular de vegetais, dentre delas a endoglucanase(XIONG et al, 2017), a β-glucosidase(PARK et al, 2016) e as xilanases(LUNKES, 2015;SILVA et al, 2016). Também há relatos do uso de 1% de ácido tânico como única fonte de carbono para induzir a produção de tanase, alcançando uma produção da enzima de até 4,71U/mL após 24 horas de fermentação em meio Czapek-dox a 30 ºC e 200 rpm de agitação (BATRA; SAXENA, 2005).Este fungo também foi capaz de degradar corante azul(HEFNAWY et al, 2017) e vermelho congo. Na degradação de vermelho congo, o fungo foi capaz de produzir oxirredutases, tais como as enzimas lignina peroxidase, azo redutase,…”
unclassified